2005
DOI: 10.1590/s0100-879x2005000700005
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cell shape and desmin intermediate filament distribution are associated with down-regulation of desmin expression in C2C12 myoblasts grown in the absence of extracellular Ca2+

Abstract: Desmin is the main intermediate filament (IF) protein of muscle cells. In skeletal muscle, desmin IFs form a scaffold that interconnects the entire contractile apparatus with the subsarcolemmal cytoskeleton and cytoplasmic organelles. The interaction between desmin and the sarcolemma is mediated by a number of membrane proteins, many of which are Ca 2+ -sensitive. In the present study, we analyzed the effects of the Ca 2+ chelator EGTA (1.75 mM) on the expression and distribution of desmin in C2C12 myoblasts g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The knockdown of muscle-specific caveolin causes the disorganization of membrane microdomains and muscle dystrophy (Galbiati et al 2001). We have previously demonstrated that disorganization of lipid rafts by treatment with the cholesterol-sequestering drug methyl-beta-cyclodextrin leads to alterations in the structural and signaling aspects of myogenesis (Mermelstein et al 2005;Mermelstein et al 2007;Portilho et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The knockdown of muscle-specific caveolin causes the disorganization of membrane microdomains and muscle dystrophy (Galbiati et al 2001). We have previously demonstrated that disorganization of lipid rafts by treatment with the cholesterol-sequestering drug methyl-beta-cyclodextrin leads to alterations in the structural and signaling aspects of myogenesis (Mermelstein et al 2005;Mermelstein et al 2007;Portilho et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Ultrastructural studies of skeletal muscles of animals affected following ionophore exposure reported myofibrillar degeneration and necrosis, with disrupted contractile apparatus [ 22 , 23 ]. The disruption in the desmin intermediate filament network observed in the current study could thus contribute to the myofibrillar degeneration previously reported, as desmin is primarily associated with the Z-disk of striated muscle [ 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 62%
“…After monensin and salinomycin exposure, the desmin intermediate filament aggregated perinuclearly ( Figure 4 ). Desmin is a critical component in the myofiber network, and various myopathies are associated with its disruption and aggregation [ 27 ]. Additionally, desmin plays a role in determining the intracellular location of mitochondria and regulating their respiratory function [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost no colocalization of CCT5 with desmin was observed in the extracellular matrix of affected tissue αB-crystallin signal was weaker than in healthy tissue αB-crystallin was present as light bands in longitudinal sections and as precipitates with desmin in the sarcoplasm Colocalization of αB-crystallin and desmin was reduced by half in affected muscle, compared with healthy muscle Hsp90 was present but appeared with an irregular pattern similar to that of desmin Hsp90 and desmin colocalization was reduced in the affected muscle, compared with healthy muscle and desmin, but it is known that desmin damage/disturbance/absence are closely related to morphological alterations of skeletal muscle fibers [18,19].…”
Section: Molecular Abnormalities Associated With Cct Chaperonopathymentioning
confidence: 99%